Penguatan Etika Digital Melalui Pembelajaran: Studi Pada Materi Adab Bersosial Media di MTs Roudlotusysyubban - Syafikah, Nurul; Sumadi, Eko (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
The pervasive use of social media among adolescents has created an urgent need for digital ethics education to mitigate negative behaviors like cyberbullying, hate speech, and the spread of misinformation. While previous studies have highlighted the importance of digital ethics, a significant gap remains in developing pedagogical strategies that are specifically tailored to the digital-native characteristics of today's students and that move beyond theoretical instruction to practical, value-internalizing methods. This research addresses that gap by investigating the application of digital ethical values through the subject of Social Media Manners, utilizing contextual learning methods video screenings and card sort designed to resonate with contemporary learners. Employing a qualitative descriptive method, data were gathered via observation, interviews, and documentation involving Akidah Akhlak teachers and 23 eighth-grade students at MTs Roudlotusysyubban. The results demonstrate that the integration of these methods positively impacts students' cognitive, affective, and psychomotor domains. Findings indicate heightened awareness in information filtering, the use of more polite language, and proactive sharing of positive content. Video screenings proved effective in providing visual and emotional stimuli for internalizing etiquette values, while the card sort method fostered active participation and critical thinking. This study concludes that contextual learning in Akidah Akhlak is a strategic and effective means of strengthening students' digital character in the current era